Ethno Gastronomy Simbolic of Indonesian Ethnic Chinese Culture at Jakarta Old Town - Manik Sunuantari; Nurul Haniza; Arry Rahayunianto (Jurnal Komunikasi Ikatan Sarjana Komunikasi Indonesia, 2019)
One of the ways to increase the country's foreign exchange earnings is encouraging tourism. As one of the countries that is rich in culinary taste of the archipelago, Indonesia has the potential to develop cultural gastronomy as one of the determining factors for tourists to choose tourist destinations. This study aims to determine the symbolic meaning of gastronomy in the culture of ethnic Chinese in Indonesia. The theory used in this study is the symbolic interactionism theory and cultural gastronomy. This study employs a case study method by selecting the  Kota Tua (Old Town) area as the research site. Data were collected by means of observation and interviews with informants related to the purpose of the research. The conclusion shows that the Chinese gastronomic culture in Indonesia is the assimilation and acculturation of Chinese and Indonesian gastronomic culture. Thus, it presents   culinary tastes that are different from the original, namely  Ethno Gastronomy of Ethnic Chinese in Indonesia.